Global and regional epidemiology of HIV-1 recombinants in 1990–2015: a systematic review and global survey. Issue 11 (November 2020) - Hemelaar, Joris; Elangovan, Ramyiadarsini; Yun, Jason; Dickson-Tetteh, Leslie; Kirtley, Shona; Gouws-Williams, Eleanor; Ghys, Peter D; ,; Abimiku, Alash'le G; Agwale, Simon; Archibald, Chris; Avidor, Boaz; et al.
Summary: Background: Global HIV-1 genetic diversity and evolution form a major challenge to treatment and prevention efforts. An increasing number of distinct HIV-1 recombinants have been identified worldwide, but their contribution to the global epidemic is unknown. We aimed to estimate the global and regional distribution of HIV-1 recombinant forms during 1990–2015. Methods: We assembled a global HIV-1 molecular epidemiology database through a systematic literature review and a global survey. We searched the PubMed, Embase (Ovid), CINAHL (Ebscohost), and Global Health (Ovid) databases for HIV-1 subtyping studies published from Jan 1, 1990, to Dec 31, 2015. Unpublished original HIV-1 subtyping data were collected through a survey among experts in the field who were members of the WHO–UNAIDS Network for HIV Isolation and Characterisation. We included prevalence studies with HIV-1 subtyping data collected during 1990–2015. Countries were grouped into 14 regions and analyses were done for four time periods (1990–99, 2000–04, 2005–09, and 2010–15). The distribution of circulating recombinant forms (CRFs) and unique recombinant forms (URFs) in individual countries was weighted according to the UNAIDS estimates of the number of people living with HIV in each country to generate regional and global estimates of numbers and proportions of HIV-1 recombinants in each time period. The systematic review is registered with PROSPERO, CRD42017067164. Findings: Our global data collection yielded an HIV-1 molecular epidemiology database of 383 519 samples from 116 countries in 1990–2015. We found that the proportion of recombinants increased over time, both globally and in most regions, reaching 22·8% (7 978 517 of 34 921 639) of global HIV-1 infections in 2010–15. Both the proportion and the number of distinct CRFs detected increased over time to 16·7% and 57 CRFs in 2010–15. The global and regional distribution of HIV-1 recombinants was diverse and evolved over time, and we found large regional variation in the numbers (0–44 CRFs), types (58 distinct CRFs), and proportions (0–80·5%) of HIV-1 recombinants. Globally, CRF02_AG was the most prevalent recombinant, accounting for 33·9% (2 701 364 of 7 978 517) of all recombinant infections in 2010–15. URFs accounted for 26·7% (2 131 450 of 7 978 517), CRF01_AE for 23·0% (1 838 433), and other CRFs for 16·4% (1 307 270) of all recombinant infections in 2010–15. Although other CRFs accounted for small proportions of infections globally (<1% each), they were prominent in regional epidemics, including in east and southeast Asia, west and central Africa, Middle East and north Africa, and eastern Europe and central Asia. In addition, in 2010–15, central Africa (21·3% [243 041 of 1 143 531]), west Africa (15·5% [838 476 of 5 419 010]), east Africa (12·6% [591 140 of 4 704 986]), and Latin America (9·6% [153 069 of 1 586 605]) had high proportions of URFs. Interpretation: HIV-1 recombinants are increasingly prominent in global and regional HIV epidemics, which has important implications for the development of an HIV vaccine and the design of diagnostic, resistance, and viral load assays. Continued and improved surveillance of the global molecular epidemiology of HIV is crucial. Funding: None.